Antibacterial and Antioxidant Activities of Derriobtusone A Isolated from Lonchocarpus obtusus. (1st June 2014) - Vasconcelos, Mayron Alves; Arruda, Francisco Vassiliepe Sousa; de Alencar, Daniel Barroso; Saker-Sampaio, Silvana; Albuquerque, Maria Rose Jane Ribeiro; dos Santos, Hélcio Silva; Bandeira, Paulo Nogueira; Pessoa, Otília Deusdênia Loiola; Cavada, Benildo Sousa; Henriques, Mariana; Pereira, Maria Olivia; Teixeira, Edson Holanda
Abstract : This study evaluated the effect of derriobtusone A, a flavonoid isolated from Lonchocarpus obtusus, on two important pathogenic bacteria, Staphylococcus aureus and Escherichia coli, as well as its antioxidant activity and toxicity. Planktonic growth assays were performed, and the inhibition of biofilm formation was evaluated. In addition, antioxidant activity was assessed by DPPH radical scavenging assay, ferrous ion chelating assay, ferric-reducing antioxidant power assay, and β -carotene bleaching assay. Toxicity was evaluated by the brine shrimp lethality test. Results showed that derriobtusone A completely inhibited the planktonic growth of S. aureus at 250 and 500 μ g/mL; however, it did not have the same activity on E. coli . Derriobtusone A reduced the biomass and colony-forming unit (cfu) of S. aureus biofilm at concentrations of 250 and 500 μ g/mL. In various concentrations, it reduced the biofilm biomass of E. coli, and, in all concentrations, it weakly reduced the cfu. Derriobtusone A showed highly efficient antioxidant ability in scavenging DPPH radical and inhibiting β -carotene oxidation. The compound showed no lethality to Artemia sp. nauplii. In conclusion, derriobtusone A may be an effective molecule against S. aureus and its biofilm, as well as a potential antioxidant compound with no toxicity.